Αγγλικά - The Wheelchair 1 - ΣΤ' Δημοτικού Επ. 129 (Υπουργείο Παιδείας και Θρησκευμάτων, 2020)
: clears sound Hello everyone, my name is Agapi Dendaki and today we are going to do a lesson, an English lesson, Based on a script by Luc Prodromo. Our lesson is called ''The Wheelchair'' and this is a wheelchair. Okay, it's a chair with wheels that helps people with disabilities move around. First of all, I would like you to meet two friends of mine. Let's look at them. Who are they? This is Luc and this is David. Now, who are these people? Luc is a conference organizer and David is a plenary speaker. What does that mean? Do you know? What do they do? Luc organizes conferences and David speaks in plenaries. And you still don't know what I'm talking about, right? What is a conference and what is a plenary? Let's see. A conference is an event. It's an event where people gather, lots of people gather in a place and they learn new things, they exchange ideas and they share their interests. They must share the same interests. For example, there are conferences for teachers, there are conferences for doctors, even YouTubers have got conferences. They actually meet in a place, not online, but in a hotel, for example. And in a conference, sometimes there are workshops. In a workshop, a small group of people meet in a room and they learn something practical. They learn something new but practical and they can't be too many in the same room. And there are also, in a conference, there are also plenaries. A plenary session takes place in a very big room with lots of people. All the people who are in the conference meet there because there is someone important who is speaking and they want to listen to this important person. That's why the room is usually an amphitheatre. The seating is inclining and so that people can all see the speaker and listen to him. Now, the plenary speaker is very often a professor. A professor is a teacher but he doesn't teach little children, he teaches big children in a university. So, let's see, what is happening today? What is happening today? We are going to use these words to talk about what is happening today. Plenary, professor, amphitheatre, conference, workshops and university. So, let's see what is happening today. Look, is organizing a big international, what? Conference. On people with disabilities. There will be a lot of speakers from all over the world. A very famous professor from Harvard University will give the first plenary talk. The talk is going to be in the big amphitheatre. There will also be a lot of practical workshops which will be for a maximum of 20 people. So, we said that the conference is on people with disabilities. What are people with disabilities? What are disabilities? There are many kinds of disabilities. For example, there are deaf people who cannot hear well, there are blind people who cannot see well and there are people who cannot move their arms or their legs, so they cannot walk or run around easily or at all maybe. They've got a mobility handicap. Now, these disabled people have got special needs and sometimes they need help. They need an assistant. An assistant can be, for example, a translator, a sign language translator who helps deaf people understand what somebody is saying because they know sign language. An assistant can be a dog, a guide dog for blind people to guide them around or an assistant can be a nurse to help all these people and people with mobility problems. Now, people with special needs may also need special equipment, that is special devices or special machines that help them do things and special arrangements. For instance, look at this school. Can you see the stairs in the middle, in front there? Can people with mobility problems climb up these stairs? Of course, they cannot. So, they need a ramp. There is a ramp there to the right where people using wheelchairs can use this ramp and get in the building, so they have access to the building. So, this school has got a ramp, so it's access friendly for people with mobility problems. So, now we've learned a number of words. Let's see, what did we know? What do we know now about people with disabilities and their difficulties? Let's see, let's use these words. Ramp, access, disabilities, assistant, equipment, wheelchair and mobility. So, let's talk about people with disabilities. Use these words. People with disabilities usually need special equipment. For example, people with mobility handicap need a wheelchair to sit in and move around. Also, if they want to get in a building, there must be a ramp for them to use. Buildings without ramps are not access friendly. The question is, do disabled people always need an assistant that is a person to help them to do things? Let's find out. You remember David. This is David. What kind of disability has he got? As you can see, he's sitting in a wheelchair because he has got a mobility handicap. And remember that Luke is a conference organizer and David is a plenary speaker. And today is this big conference and David is going to give a talk and Luke is waiting for him. Here is the moment when they meet for the first time. Let's watch them meeting. Hi, I'm David and this is... Hi, pleased to meet you. Yes, pleased to meet you. Luke, Luke Medler, conference organizer, just waiting for our plenary speaker, very important professor, you know. Well, actually... Yes, it must be very difficult for him. Yes, things could be better. It must be a hard life. I've got a cousin who's handicapped, so I know what it's like. He needs a lot of attention. Can't do a thing on his own. Pity. It's incredibly hard on the family. So, let's talk about what we saw here on this video. Let's answer these questions. Where are Luke and David? At the supermarket, at a conference or at a school? They are at a conference. What's the weather like today? Is it cold, is it raining or is it very warm? It's very warm. Luke says that it's hot, hot, very hot today. David is holding what? A bag, a book or a tablet? He's holding a bag. Luke and David are friends, strangers or cousins? They are strangers. They have never met before. This is their first time. Luke has got a cousin with an easy life, no family or a handicap? His cousin has got a handicap. Luke says, pleased to meet you, but to whom? To his cousin, to David's friend or to David? Yes, he says pleased to meet you to David's friend. David's friend is there, but we can't see him. And when Luke says pity, what feelings does he express about his disabled cousin? What does he mean with the word pity? He feels sorry for him? He feels proud of him? Or he's happy about him? He feels sorry for him. When we pity someone, we feel sorry for them. Poor you. Now that was a very big mistake. Luke is making a mistake here because we must not pity people with disability. They don't need our pity. They need our respect. So we behave to people with disabilities with respect. Now, you are going to watch the video, the whole video and find all the ways that Luke behaves disrespectfully towards David. It's hot today. Oh, dear. Excuse me, do you mind? Oh, sorry. Sorry. Thank you. Hi, I'm David and this is... Hi, pleased to meet you. Yes, pleased to meet you. Luke, Luke Medler, conference organizer. Just waiting for our plenary speaker. Very important professor, you know. Well, actually... Yes, it must be very difficult for him. Yes, things could be better. It must be a hard life. I've got a cousin who's handicapped, so I know what it's like. He needs a lot of attention. Can't do a thing on his own. Pity. It's incredibly hard on the family. What does he do? I teach. Oh, a teacher. Well, that must be very hard. No, not really. Well, really, good for you. I mean, it's so difficult nowadays. I mean, there's so much running around to do. I mean, moving around. And kids, they're so, you know, and him being, you know... It's not really a problem. I can manage, you know. Is there a ramp? A ramp? You know, at the school, you know, for handicapped people. Yes. The students campaign for one, and now the whole school is disabled access friendly. Ah, that's good. What does he teach? I teach English. English, eh? Oh, that is very interesting. Well, it wouldn't be gymnastics, would it? As a matter of fact, there are a lot of gym teachers with disabilities nowadays, you know. Oh, yes, of course, yes. Sorry. David. David? David, do you have an assistant? An assistant? To help. To help? The lessons. To help with the lessons? To help with the lessons. No. I teach alone. I can manage. Oh, you do it on your own, do you? Oh, tough. Pity. I mean, don't the kids misbehave? No more than usual. I mean, you just need to motivate them, as always. I mean, they don't, you know, pull your leg, to coin a phrase. Was it an accident? An accident? An accident? The wheelchair. The wheelchair. No, I chose it. Ah, I see. How long has he been handicapped? I mean, differently abled. Must watch our language, eh? Political correctness and all that. Look, do you think we could see the amphitheatre now, please? I'd like to check the equipment, if that's all right. Yes, yes, that's okay, but I do have to wait here for our plenary speaker. Our main speaker, if you know what I mean. Yes, I do know what you mean. Well, I wonder where he's got to. Look, I would like to check the PowerPoint equipment, please. Well, yes, it is time we started, actually. We are running late. I mean, we are late. It's time we, you know, go. Shall I take your bag for you? No, thank you. Are you sure? I'd rather hang on to it, if you don't mind. It's got the notes for my talk in it. Okay, I'll take the wheelchair for you. Thank you. It's not necessary. No, please. Are you all right? Okay, all right, I understand. So, yes. You're giving a talk too, are you? What will it be? A little workshop? It's my plenary talk. It's called Respect and Understanding for Wheelchair Users. Some tips. Respect. Understanding. Plenary. But I thought Professor Johnson's plenary was also... Excuse me. Johnson. David Johnson. Dr David Johnson. David. You're David. David Johnson, Cambridge University Professor. Yes, you're David Johnson. You're our plenary speaker. You're going to give the first plenary. Well, well, well. Welcome. Thank you. Shall we... Shall I... Can I take your bag for you? No, thank you. Give me a hand. Let me give you a hand. No, you don't need to. I'll take your bag. No, I can manage. Okay. Thank you. I'll just take the wheelchair. No, no. It's my pleasure. No, thank you. Allow me. It's all right. My pleasure. Sorry. I thought you couldn't walk. Look, let me explain. I've recently developed a condition which prevents me from standing upright for long periods and from walking without great difficulty, so I'm now very often a wheelchair user, but not all the time. There are different kinds of disability, you know. Yes, yes, of course, of course. Yes, Professor Johnson. Indeed. Now, if we could see the room now, please. Yes, of course, Dr Johnson, please. Follow me. This way, please. Just follow me. So we saw how David and Luke met for the first time. Now they are going for the conference and let's see if these facts are true or false. David says that life is difficult. Is that true or false? It's false. Luke says that life is difficult. At first, Luke thinks that David is not an important person. Yes, that's right. He thinks that who is David? A person in a wheelchair. Nobody. Luke's cousin has a physical disability. Yes, that's true. He's got disability. There is a ramp in David's school. Yes, there is a ramp because the children campaigned for it. They asked for it. David has problems with his students. No, this is false. He has no more problems than usual. David wants to go to the conference room. Yes, it's true. He wants to go to the conference room because he's the plenary speaker. Luke carries David's bag. No, that's not true. He wants to carry it. He offers to carry it but David doesn't want him to carry it. He wants to hang on to it. David can't walk. No, that's false. Although David is a wheelchair user, he can walk. It's just that he cannot walk for a long time, not without difficulty and he cannot be standing up for a long time. So sometimes we don't know what people with disabilities can or cannot do. Did you also notice that Luke made lots of mistakes as he was speaking to David? Lots of them, not just one or two but many mistakes. We're going to talk about these mistakes in our next lesson. So see you soon. [♪ Music playing in the background for the duration of the video. The end.